2016
DOI: 10.15403/jgld.2014.1121.253.uks
|View full text |Cite
|
Sign up to set email alerts
|

Should we Investigate Gastroenterology Patients for Pancreatic Exocrine Insufficiency? A Dual Centre UK Study

Abstract: Background & Aims: Pancreatic exocrine insufficiency may be under recognised in gastroenterological practice. We aimed to identify the prevalence of pancreatic insufficiency in secondary care gastroenterology clinics and determine if co-morbidity or presenting symptoms could predict diagnosis. A secondary aim was to assess response to treatment. Methods: A dual centre retrospective analysis was conducted in secondary care gastroenterology clinics. Patients tested for pancreatic exocrine insufficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…3 Among 238 patients with abnormal FEL-1 who went on to further assessment, 34.2% showed changes consistent with CP on subsequent cross-sectional imaging reflecting undiagnosed CP as a cause. 3 This is in keeping with post mortem studies showing a higher prevalence of CP than clinically reported. 4,5 Of the 61.8% of 238 patients with low FEL-1 who were followed up and treated with PERT, 79.6% reported symptomatic improvement.…”
Section: Letter: the Under-treatment And Under-diagnosis Of Pancreatimentioning
confidence: 97%
“…3 Among 238 patients with abnormal FEL-1 who went on to further assessment, 34.2% showed changes consistent with CP on subsequent cross-sectional imaging reflecting undiagnosed CP as a cause. 3 This is in keeping with post mortem studies showing a higher prevalence of CP than clinically reported. 4,5 Of the 61.8% of 238 patients with low FEL-1 who were followed up and treated with PERT, 79.6% reported symptomatic improvement.…”
Section: Letter: the Under-treatment And Under-diagnosis Of Pancreatimentioning
confidence: 97%
“…There are limited reliable data on the prevalence of PEI in the general population 5 . PEI often goes undetected and patients referred from primary care may not represent the majority of PEI sufferers within the community 3 , 4 , 17 , 18 …”
Section: Recommendationsmentioning
confidence: 99%
“…The symptoms of PEI are gastrointestinal‐related and non‐specific. If undiagnosed, patients may have ongoing symptoms such as diarrhoea and abdominal pain that can sometimes be mistaken as a functional bowel disorder 3 , 18 . PEI symptoms can vary from patient to patient, and are dependent on the degree of PEI experienced and its aetiology 5 …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 It is estimated that 80% of patients respond clinically, and PERT has been shown to relieve the symptoms of PEI and improve survival. [6][7][8] However, studies have shown that treatment is initiated in as few as 21% of patients who might benefit, and that dosing may be inadequate in many patients on treatment. 9,10 However, the factors predicting initiation of, and response to, PERT are unknown.…”
Section: Introductionmentioning
confidence: 99%